The Concepts of 心xīn - Pichetsilpa, Pattra (Journal of Sinology (วารสารจีนวิทยา), 2011)
Following the theory of cognitive semantic and the cultural conception of心xīn, this paper aims to describe the concepts of心xīn in present-day Chinese. The study finds out that there is a rich cultural history shaping the Chinese concept of心xīn. 心xīn is conceptualized as the thinking and feeling agent. It is also a place where thoughts and feelings have situated. Finally, 心xīn is conceptualized as the ruler of human body. In a way, all kinds of human’s behavior are controlled by心xīn. The main factor that formed the concepts of心xīn is the cultural belief.